2022
DOI: 10.3390/ijms232416188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Heating on the Monomer Elution and Porosity of Conventional and Bulk-Fill Resin-Based Dental Composites

Abstract: The pre-heating of dental resin-based composites (RBCs) improves adaptability to cavity walls, reducing microleakages. However, the rapid cooling of the pre-heated RBC may change the polymerization kinetics, and thus the final network configuration of the RBC. It is well known that unreacted monomers remaining in the set RBC can leach into the oral cavity. However, it is still not clear how the pre-heating and cooling of RBCs alter monomer elution (ME). Thus, the purpose was to determine the ME from room-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 54 publications
(81 reference statements)
2
15
0
Order By: Relevance
“…In the present study, preheating of bulk-fill composites significantly reduced the amount of monomer elution, which is consistent with previous studies. 11 , 29 Dunavári et al 29 found that preheating significantly reduced the amount of UDMA and BisGMA monomer elution from Filtek One Bulk Fill Restorative composite resin, similar to the present study. In contrast, monomer elution increased when conventional composite resins were preheated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, preheating of bulk-fill composites significantly reduced the amount of monomer elution, which is consistent with previous studies. 11 , 29 Dunavári et al 29 found that preheating significantly reduced the amount of UDMA and BisGMA monomer elution from Filtek One Bulk Fill Restorative composite resin, similar to the present study. In contrast, monomer elution increased when conventional composite resins were preheated.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, elution of BisGMA was also detected; even though it was not listed in the monomers specified by the manufacturer, UDMA elution was higher than that in previous studies. 28 , 29 BisGMA exhibits high viscosity owing to its high molecular weight and strong intramolecular hydrogen bonding ability. However, the lower viscosity and higher double bond concentration of UDMA results in a high degree of conversion and crosslinking density.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found distinct monomer release from preheated conventional RBCs stratified in 2 mm layers compared to 4 mm thick bulk-fill RBCs [ 16 ]. The extent of leached monomers from the tested room temperature bulk-fill RBC samples was significantly greater compared to the preheated specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of leached monomers from the tested room temperature bulk-fill RBC samples was significantly greater compared to the preheated specimens. In contrast, stratified conventional RBCs showed an increased monomer elution from the preheated samples [ 16 ]. However, it was concluded that the absolute amount of eluted resinous substances was strongly dependent on the RBC’s composition and not related to the mode of application [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation